S1PR3-driven positive feedback loop sustains STAT3 activation and keratinocyte hyperproliferation in psoriasis - Panpan Lian; Li Li; Renwei Lu; Bin Zhang; Junaid Wazir; Chaode Gu; Bojie Ma; Wenyuan Pu; Wangsen Cao; Zhiqiang Huang; Zhonglan Su; Hongwei Wang (Cell Death and Disease)
Abstract Psoriasis is a chronic inflammatory skin disorder characterized by hyperproliferation of keratinocytes and persistent inflammation. Although persistent activation of signal transducer and activator of transcription 3 (STAT3) is implicated in its pathogenesis, the mechanisms underlying the sustained STAT3 activation remain poorly understood. Here, we identify sphingosine-1-phosphate receptor 3 (S1PR3) as a critical regulator of STAT3 activation and psoriasis pathogenesis, orchestrating a self-amplifying circuit that sustains keratinocyte hyperproliferation and chronic inflammation. S1PR3 expression is markedly elevated in psoriatic lesions and correlates with disease severity. Using genetic and pharmacological approaches, we reveal a novel S1PR3–Src–STAT3 signaling axis that drives both early and prolonged STAT3 activation in keratinocytes. Mechanistically, S1PR3 operates through Gαi/PKA-mediated Src activation, enhancing STAT3 phosphorylation and subsequent transcriptional activity. Importantly, we reveal a previously unrecognized positive feedback loop wherein activated STAT3 directly upregulates S1PR3 expression, perpetuating inflammation and hyperproliferation. Genetic deletion of S1pr3 in mice or pharmacological inhibition of S1PR3 significantly attenuates psoriasis-like skin inflammation, decreasing epidermal hyperplasia, dermal angiogenesis, and inflammatory mediator production. These findings provide new insights into the molecular mechanisms underlying psoriasis and identify S1PR3 as a promising therapeutic target. Our study suggests that disrupting the S1PR3–STAT3 feedback loop may offer a novel strategy for treating psoriasis and potentially other chronic inflammatory diseases driven by persistent STAT3 activation.